Gambaran Kesiapsiagaan Perawat dalam Manajemen Bencana di Puskesmas Kota Padang: Nurses' Preparedness in Disaster Management at Health Centers in Padang City - Elvi Oktarina; Fiziola; Fitri Mailani (Fakultas Keperawatan Universitas Andalas, 2024)
Nurses at public health centers play a crucial role in mitigating the impact of disasters, but their preparedness for handling emergency situations is often not optimal. In Padang City, a study was conducted to assess the level of preparedness among nurses in disaster management. Using a quantitative approach, data were collected from 138 nurses working in 24 public health centers through a stratified random sampling method. The results showed that 58% of the nurses had a high level of preparedness. More specifically, 58% had good knowledge of disaster management, 74.6% displayed a positive attitude, and 68.8% practiced good disaster management techniques. These findings indicate that public health center nurses in Padang City are generally well-prepared in terms of knowledge, attitude, and practice. However, further improvement is still needed. Increasing the number of trained nurses and providing regular disaster management training are recommended to enhance preparedness in disaster response.